The effects of poling on physiological, kinematic and kinetic responses in roller ski skating - Grasaas, E.; Hegge, A. M.; Ettema, G.; Sandbakk, O. (European Journal of Applied Physiology, 2014)
Purpose We investigated the effects of poling on physiological, kinematic and kinetic responses in the G4 skating technique where the poling movement is synchronized with the leg push-off on one side (strong side) followed by a forward arm swing during the leg push-off on the other side (weak side). Methods G4 skating with (G4-P) and without (G4-NP) poling was compared in 17 elite male cross-country skiers during 4-min submaximal tests on a 2 % inclined roller ski treadmill at 10, 15 and 20 km/h. Results G4-P demonstrated less ventilatory stress and higher gross efficiency compared to G4-NP at all velocities, and the blood lactate concentration was lower at the high velocity (all P < 0.05). Furthermore, longer cycle lengths and lower cycle rates were found with G4-P at all velocities, with correspondingly lower peak ski forces, increased ski velocities and less angling and edging of the skis (all P < 0.05). The peak ski forces on the strong side were lower than on the weak side with G4-P at all velocities (all P < 0.05), but no differences between the sides were found with G4-NP. Conclusions The reduced physiological cost, higher gross efficiency and longer cycle lengths together with the lower ski forces at a given work rate with G4-P demonstrate the effectiveness of poling in the G4 skating technique. Thus, poling provides possibilities to increase total propulsion, to reduce ski forces and to enhance skiing efficiency.